A Systematic Review of Examining the Significance and Functions of Clinical Pharmacy Services for Patients with Chronic Kidney Disease - Ghuffah, Adel Mohmmed; Hendi, Mazen Mohammed; Ebrahim, Osama Abdu; Fakher, Abulaziz Dhaifallah; Jeli, Ali Yahya; Dighriri, Ibrahim Mohammed; AL-Ghamdi, Samah Saeed; Alnomani, Hamad Hamdan; Alyuhyuwa, Mohammad Said; Alghamdi, Ahmed Mouhammed; Alharbi, Naif Olaythah; Algohani, Ahmad Mohammad; et al. (Journal of Ecohumanism, 2024)
Clinical pharmacy services (CPS) are essential for individuals with chronic kidney disease (CKD) not only to reduce morbidity and mortality but also to alleviate the economic burden. A systematic review was conducted to evaluate the impact of CPS on adult patients with CKD. This review examined randomized controlled trials (RCTs) published between 2013 and 2023, sourced from PubMed, Web of Science, and Scopus databases. The Cochrane Risk of Bias Tool 2.0 was employed to assess the quality of these studies. Five studies involving 2,738 patients with CKD at various stages indicated that CPS roles encompassed medication review, patient education, and collaboration with physicians. Furthermore, CPS facilitated improved medication reconciliation, safety, and quality of life (QoL). Clinical outcomes varied across studies; some reported improvements in interdialytic weight gain, blood pressure control, and hemoglobin levels, whereas others showed no significant difference in blood pressure management. The inconsistent results across studies highlight the need for additional research to enhance these interventions and assess their long-term effects on CKD management. However, the potential of CPS to reduce expenses in CKD management is a promising aspect that cannot be overlooked.